The Effect of Rice Bran Extract on Arterial Blood Pressure, Hepatic Steatosis, and Inflammation in Mice Fed with a High-Fat Diet - Naphatsanan Duansak; Pritsana Piyabhan; Umarat Srisawat; Jarinyaporn Naowaboot; Nusiri Lerdvuthisopon; Geert Schmid-Schönbein (Journal of Nutrition and Metabolism)
Background. Inflammation and hypertension are primary mechanisms involving in obesity-associated adverse effects of a high-fat diet. The aim of this study was to evaluate the effects of rice bran extract (RBE) on arterial blood pressure, hepatic steatosis, inflammation, and oxidative stress in high-fat diet (HFD)-induced obese mice. Methods. Male ICR mice were divided into four groups, including a normal-diet control group, a high-fat diet (HFD) (60% kcal from fat) group, an HFD group treated with RBE (220 mg/kg/day), and an HFD group treated with 1100 mg/kg/day for eight weeks. Besides body weight and arterial blood pressure, we determined liver values of total cholesterol, triglyceride, as well as percent body fat, tumor necrosis factor-α (TNF-α), malondialdehyde (MDA), nuclear factor kappa-B (NF-κB), matrix metalloprotease-9 (MMP-9), cyclooxygenase-2 (COX-2), and mRNA endothelial nitric oxide synthase (eNOS). Results. The HFD group had increased body weight, increased systolic and diastolic blood pressure, liver total cholesterol, triglyceride, NF-κB, COX-2 and MMP-9 protein levels, and decreased mRNA eNOS in the aorta. Mice of the HFD group receiving RBE had reduced diastolic blood pressure, as well as significantly decreased liver and serum TNF-α and MDA levels in the liver, and reduced NF-κB levels in both the liver and heart. Conclusions. These results demonstrate that RBE decreases diastolic blood pressure, the liver lipid droplet accumulation, liver and myocardial NF-κB, myocardial COX-2 and MMP-9 protein levels, and oxidative stress. Moreover, RBE may improve endothelial function and may alleviate adverse health effects associated with obesity including obesity-associated hypertension.